KECERNAAN NDF DAN ADF PAKAN LENGKAP BERBASIS TEBON JAGUNG PADA SAPI FH - Ransa, Cindy P.; Tuturoong, R. A. V.; Pendong, A.F.; Waani, M.R. (ZOOTEC, 2020)
NDF AND ADF DIGESTIBILITY OF COMPLETE FEED OF CORN FORAGE IN FH CATTLE. The purpose of this study was to determine the consumption and digestibility of NDF and ADF based on corn forage based feed in FH cattle. The experimental material used was 14 FH dairy cows, aged 7-8 years with weights between 300 - 400 kg, treatment feed, consisting of: Ra = 30% concentrate feed + 70% corn forage and treatment Rb = 30% concentrate + 35% corn forage + 35% king grass. The research method was a biological experiment, with a statistical analysis of the two-sample T test with unequal variation (t-test two sample assuming unequal varience). The results of the T test analysis showed that the NDF consumption of Rb treatment was not significantly different (P> 0.05) compared to Ra, whereas the consumption of ADF, as well as the digestibility of NDF and ADF treatment of Rb was significantly different (P <0.01) with Ra treatment. It can be concluded that the digestibility of NDF and ADF complete feed consisting of concentrate, corn forage and king grass is better, compared to complete feed consisting of concentrate and corn forage.Â Keywords: Consumption, digestibility, NDF, ADF, complete feed, FH cattle.